1st annual Colorado rare plant symposium: presentation - Panjabi, Susan Spackman, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2004)
A review of Colorado's Federally listed and candidate plant species. Includes a discussion and presentation of Colorado's threatened, endangered, candidate, and petitioned species.
Astragalus humilimus: Mancos milkvetch
First annual Colorado rare plant symposium: presentation
Symposium held on September 17, 2004 at the Olympian Hall in Steamboat Springs, Colorado.
Title from "Minutes from the First Annual Colorado Rare Plant Symposium."
Keywords: Rare plants -- Colorado -- Identification; Endemic plants -- Colorado -- Identification; Endangered plants -- Colorado -- Identification